2020
DOI: 10.3389/fpsyt.2020.487200
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events in Different Social Contexts Are Associated With Self-Injury From Early Adolescence to Early Adulthood

Abstract: Self-injury often arises as a maladaptive coping strategy used to alleviate distress. Past research has typically examined how chronic stressors in a specific context are associated with self-injury. Little is known about the unique and cumulative associations between acute stressful life events that occur in different social contexts and self-injury among adolescents. This is especially the case for males, for whom the etiology of self-injury is understudied. We examine the unique and cumulative contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…In a prior study based on the same sample used here, we found that some secondary consequences of the pandemic (e.g., economic disruptions) increased the risk of young adults' perceived stress, internalizing symptoms, and anger (Shanahan et al., 2020 ). While the experience of one stressor at a time may be relatively manageable, an accumulation of stressors is likely to become so stressful that engagement in maladaptive behaviors is increasingly likely (Appleyard, Egeland, Van Dulmen, & Sroufe, 2005 ; Steinhoff, Bechtiger, Ribeaud, Eisner, & Shanahan, 2020 ). However, the associations of (1) cumulative pandemic‐related stressors (e.g., exposure to the disease, financial difficulties, disruptions of work and educational arrangements) and (2) prepandemic stressors (e.g., stressful life events) with during‐pandemic self‐injury and domestic violence have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study based on the same sample used here, we found that some secondary consequences of the pandemic (e.g., economic disruptions) increased the risk of young adults' perceived stress, internalizing symptoms, and anger (Shanahan et al., 2020 ). While the experience of one stressor at a time may be relatively manageable, an accumulation of stressors is likely to become so stressful that engagement in maladaptive behaviors is increasingly likely (Appleyard, Egeland, Van Dulmen, & Sroufe, 2005 ; Steinhoff, Bechtiger, Ribeaud, Eisner, & Shanahan, 2020 ). However, the associations of (1) cumulative pandemic‐related stressors (e.g., exposure to the disease, financial difficulties, disruptions of work and educational arrangements) and (2) prepandemic stressors (e.g., stressful life events) with during‐pandemic self‐injury and domestic violence have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Several z-proso studies have specifically examined internalising symptoms, self-harm, and suicidality, with a focus on the transition from early adolescence to early adulthood. One study showed that 27% of young people reported self-harm at least once between ages 13 and 20 (Steinhoff et al, 2020). Precursors of recurrent self-harm included early internalising symptoms and early self-injury onset (Steinhoff et al, 2021).…”
Section: Internalising Symptoms Self-harm and Suicidalitymentioning
confidence: 99%
“…Precursors of recurrent self-harm included early internalising symptoms and early self-injury onset (Steinhoff et al, 2021). The risk of self-harm increased with an increasing number of life events (Steinhoff et al, 2020). Less than half of the adolescents with self-injury contacted mental health services (Steinhoff et al, 2021).…”
Section: Internalising Symptoms Self-harm and Suicidalitymentioning
confidence: 99%
“…Sex differences in susceptibility to social isolation and social stress are also observed during the adolescent period. In humans, adolescent girls are more likely than adolescent boys to be sensitive to social stress, become depressed, or to engage in self-injurious behavior following stress in peer and/or family relationships ( 191 , 192 ). In adolescent male mice, social isolation during adolescence leads to impaired social recognition memory in adulthood ( 193 ).…”
Section: Critical Periods and Chronic Illness: The Breakdown Of Adaptmentioning
confidence: 99%